Measurement of ψ (2S) polarisation in pp collisions at √s = 7 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (The European physical journal. C, Particles and fields, 2014)
The polarisation of prompt ψ (2S) mesons is measured by performing an angular analysis of ψ (2S)→μ+μ− decays using proton-proton collision data, corre-sponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb detector at a centre-of-mass energy of 7 TeV. The polarisation is measured in bins of transverse momentum pT and rapidity y in the kinematic region 3.5<pT<15 GeV/c and 2.0<y<4.5, and is compared to theoretical models. No significant polarisation is observed.